ERASMUS "overcoming the digital divide in Europe and southeast Asia (ODDEA)" project - UiTM, UiTM Global (Office of International Affairs (OIA), 2024)
On 9 September 2024, Dr. Azlina Hanit, Senior Lecturer in Economics at Arshad Ayub Graduate Business School (AAGBS) anda member of the ERASMUS "Overcoming the Digital Divide in Europe and Southeast Asia (ODDEA)" project, along with Professor Dr. Anetta Čaplanová, Project Coordinator and Economics Professor at the University of Economics in Bratislava, held an engagement session with several faculty members fram Széchenyi István University of Györ, in Gyorr, Hungary as part of the project's research mobility program. During the session, the researchers provideda briefing on the four-year ODDEA project and introduced their respective universities and faculties. The aim was to spark interest in inter-university collaborations, including joint research initiatives, co-teaching opportunities. conference co-organization, as well as staff and student exchange programs.